1994
DOI: 10.1111/j.1469-8137.1994.tb04259.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal accumulation and tolerance in British populations of the metallophyte Thlaspi caerulescens J. & C. Presl (Brassicaceae)

Abstract: SUMMARYHeavy metal uptake, accumulation and tolerance were investigated in five British populations of the metallophyte Thlaspi caerulescens from metalliferous sites from the north and south Pennines orefields. Analysis of field samples sbowed mean shoot Zn, Pb and Cd concentrations of up to 21 000, 660 and 164 //g g"' respectively, A solution culture experiment designed to investigate both tolerance and metal accumulation is reported. Indices of tolerance of five populations to 12 metals (Ag, A!, Cd, Co, Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
301
1
12

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 630 publications
(342 citation statements)
references
References 23 publications
10
301
1
12
Order By: Relevance
“…The high transcript levels of MTP8, MTP11 and other candidate genes with putative functions in Fe, Cu and Mn homeostasis suggest the need to adjust the homeostasis of these metals in Zn hyperaccumulators. In this context, it is interesting to note that in an experiment employing a range of different metal-supplemented nutrient solutions, T. caerulescens had the ability to not only accumulate Zn, Cd and Ni, but also other metal ions, for example Mn and Co in shoots, and Cu, Fe and Pb in roots [55].…”
Section: Uptake Into Root Cellsmentioning
confidence: 99%
“…The high transcript levels of MTP8, MTP11 and other candidate genes with putative functions in Fe, Cu and Mn homeostasis suggest the need to adjust the homeostasis of these metals in Zn hyperaccumulators. In this context, it is interesting to note that in an experiment employing a range of different metal-supplemented nutrient solutions, T. caerulescens had the ability to not only accumulate Zn, Cd and Ni, but also other metal ions, for example Mn and Co in shoots, and Cu, Fe and Pb in roots [55].…”
Section: Uptake Into Root Cellsmentioning
confidence: 99%
“…A summary of the chemical hydrolyzation reaction is shown below (11,22): (2) Therefore, by hydrolyzing these esters, we may form new binding sites that were previously unavailable to the metal ions. Table 1 shows the milligrams of metal bound by 1.0 g of alfalfa shoot biomass before and after the hydrolyzation reaction.…”
Section: Metal Binding Study With Hydrolyzed Biomassmentioning
confidence: 99%
“…The identification of several metalhyperaccumulator plant species (Baker and Brooks, 1989;Baker et al, 1998) demonstrates that the genetic potential exists for successful phytoremediation of contaminated soils. One of the best-known metal hyperaccumulators is Thlaspi caerulescens J&C Presl, which has been reported to have a great potential for extraction of Zn and Cd from metalliferous soils (Reeves and Brooks, 1983;Chaney, 1993;Baker et al, 1994;Brown et al, 1994Brown et al, , 1995aBrown et al, , 1995b. Recently, Brown et al (1995b) reported that from a hydroponic medium, T. caerulescens accumulated more than 25,000 g Zn g Ϫ1 before symptoms of Zn toxicity (i.e.…”
mentioning
confidence: 99%